Genetic history, structure and gene flow among populations of Belgica antarctica, the only free-living insect in the western Antarctic Peninsula - Hilary Edgington; Vitor A.C. Pavinato; Drew Spacht; J.D. Gantz; Peter Convey; Richard E. Lee; David L. Denlinger; Andy Michel (Polar Science, 2023)

Fine-scale variation in microhabitat conditions influences physiology and metabolism in an Antarctic insect - Drew E. Spacht; J. D. Gantz; Jack J. Devlin; Eleanor A. McCabe; Richard E. Lee; David L. Denlinger; Nicholas M. Teets (Oecologia, 2021)

Cross-tolerance and transcriptional shifts underlying abiotic stress in the seabird tick, Ixodes uriae - Benjamin Davies; Andrew J. Rosendale; Josiah D. Gantz; Richard E. Lee; David L. Denlinger; Joshua B. Benoit (Polar Biology, 2021)

Environmental factors influencing fine-scale distribution of Antarctica’s only endemic insect - Leslie J. Potts; J. D. Gantz; Yuta Kawarasaki; Benjamin N. Philip; David J. Gonthier; Audrey D. Law; Luke Moe; Jason M. Unrine; Rebecca L. McCulley; Richard E. Lee; David L. Denlinger; Nicholas M. Teets (Oecologia, 2020)
Species distributions are dependent on interactions with abiotic and biotic factors in the environment. Abiotic factors like temperature, moisture, and soil nutrients, along with biotic interactions within and between species, can all have strong influences on spatial distributions of plants and animals. Terrestrial Antarctic habitats are relatively simple and thus good systems to study ecological factors that drive species distributions and abundance. However, these environments are also sensitive to perturbation, and thus understanding the ecological drivers of species distribution is critical for predicting responses to environmental change. The Antarctic midge, Belgica antarctica , is the only endemic insect on the continent and has a patchy distribution along the Antarctic Peninsula. While its life history and physiology are well studied, factors that underlie variation in population density within its range are unknown. Previous work on Antarctic microfauna indicates that distribution over broad scales is primarily regulated by soil moisture, nitrogen content, and the presence of suitable plant life, but whether these patterns are true over smaller spatial scales has not been investigated. Here we sampled midges across five islands on the Antarctic Peninsula and tested a series of hypotheses to determine the relative influences of abiotic and biotic factors on midge abundance. While historical literature suggests that Antarctic organisms are limited by the abiotic environment, our best-supported hypothesis indicated that abundance is predicted by a combination of abiotic and biotic conditions. Our results are consistent with a growing body of literature that biotic interactions are more important in Antarctic ecosystems than historically appreciated.

The Antarctic mite, Alaskozetes antarcticus, shares bacterial microbiome community membership but not abundance between adults and tritonymphs - Christopher J. Holmes; Emily C. Jennings; J. D. Gantz; Drew Spacht; Austin A. Spangler; David L. Denlinger; Richard E. Lee; Trinity L. Hamilton; Joshua B. Benoit (Polar Biology, 2019)

Characterization of drought-induced rapid cold-hardening in the Antarctic midge, Belgica antarctica - Yuta Kawarasaki; Nicholas M. Teets; Benjamin N. Philip; Leslie J. Potts; J. D. Gantz; David L. Denlinger; Richard E. Lee (Polar Biology, 2019)

Sex- and developmental-specific transcriptomic analyses of the Antarctic mite, Alaskozetes antarcticus, reveal transcriptional shifts underlying oribatid mite reproduction - Hannah E. Meibers; Geoffrey Finch; Robert T. Gregg; Sierra Glenn; Keavash D. Assani; Emily C. Jennings; Benjamin Davies; Andrew J. Rosendale; Christopher J. Holmes; J. D. Gantz; Drew E. Spacht; Richard E. Lee; et al. (Polar Biology, 2019)

Life history traits of adults and embryos of the Antarctic midge Belgica antarctica - Eri Harada; Richard E. Lee; David L. Denlinger; Shin G. Goto (Polar Biology, 2014)

Wet hibernacula promote inoculative freezing and limit the potential for cryoprotective dehydration in the Antarctic midge, Belgica antarctica - Yuta Kawarasaki; Nicholas M. Teets; David L. Denlinger; Richard E. Lee (Polar Biology, 2014)

Expression of genes involved in energy mobilization and osmoprotectant synthesis during thermal and dehydration stress in the Antarctic midge, Belgica antarctica - Nicholas M. Teets; Yuta Kawarasaki; Richard E. Lee; David L. Denlinger (Journal of Comparative Physiology B, 2013)

A potential role for ribosomal protein S2 in the gene network regulating reproductive diapause in the mosquito Culex pipiens - Mijung Kim; David L. Denlinger (Journal of Comparative Physiology B, 2010)

Dehydration, rehydration, and overhydration alter patterns of gene expression in the Antarctic midge, Belgica antarctica - Giancarlo Lopez-Martinez; Joshua B. Benoit; Joseph P. Rinehart; Michael A. Elnitsky; Richard E. Lee; David L. Denlinger (Journal of Comparative Physiology B, 2009)

The seabird tick, Ixodes uriae, uses uric acid in penguin guano as a kairomone and guanine in tick feces as an assembly pheromone on the Antarctic Peninsula - Joshua B. Benoit; Giancarlo Lopez-Martinez; Seth A. Philips; Michael A. Elnitsky; Jay A. Yoder; Richard E. Lee; David L. Denlinger (Polar Biology, 2008)

Extremely large aggregations of collembolan eggs on Humble Island, Antarctica: a response to early seasonal warming? - Glen G. Schulte; Michael A. Elnitsky; Joshua B. Benoit; David L. Denlinger; Richard E. Lee (Polar Biology, 2008)

Shifts in the carbohydrate, polyol, and amino acid pools during rapid cold-hardening and diapause-associated cold-hardening in flesh flies (Sarcophaga crassipalpis): a metabolomic comparison - M. Robert Michaud; David L. Denlinger (Journal of Comparative Physiology B, 2007)